Perception of Tinnitus Handicap And Stress Across Age Groups in Normal Hearing. - Sharma, Anuradh; sood, Nilanshu; Munjal, Sanjay; Panda, Naresh (International Tinnitus Journal, 2021)
Introduction: This research was conducted to investigate the severity of tinnitus, its impact on subject's daily, personal and emotional life, which varies widely across the age groups. Methodology: Sample population of 60 unilateral tinnitus subjects with normal hearing between the age ranges of 15-55years were divided into four age groups. Tinnitus severity was measured using tinnitus severity index, impact of tinnitus on daily life was documented through tinnitus handicap inventory and the stress levels through perceived stress scale. Results: A high frequency tinnitus was observed in age group of 56-65years, in contrast to noise like tinnitus in subjects aged 15-25years. The tinnitus was found to be most handicapping (38-56; moderate handicap) in Group 4(56-65years), the perceived stress levels were also falling in very high range (21 and over). Tinnitus severity index did not show any significant difference between the Group 1:15-25yrs, Group 2: 26-40yrs, Group 3:41-55yrs, and however group 4(56-65 yrs) did report with mild severity. The outcomes of present study demonstrated that elderly subjects certainly require modifications in the test protocols and referrals to address to their significant responses to tinnitus.